EFFECTS OF FREE & RESTRICTED REMOBILIZATION ON THE BODYWEIGHT AND MID THIGH CIRCUMFERENCE OF RABBIT: Effects of free & Restricted Remobilization on Rabbit - Anjum, Dr Samina; Minhas, Liaqat Ali; Qamar, Khadija (Pakistan Armed Forces Medical Journal, 2010)
Objective: To find out the effects of free and restricted remobilization on the generalized body weight and mid thigh circumference of rabbit. For this purpose, knee joints of rabbits were immobilized first. Study Design: Randomized Controlled Trials (RCT) Place and Duration of the study: Study was carried out in Army Medical College, Rawalpindi and National Institute of Health Sciences, Islamabad from April 2006 to April 2007. Materials and Methods: Twenty four adult New Zealand White rabbits were randomly divided into three groups using random numbers table. Group I served as a control group whereas the left knee joint along with ankle joint of the experimental groups II & III were immobilized in extension in a plaster of Paris cast for 4 weeks. At the end of 4 weeks plaster cast was removed and group II i.e. free mobility group and group III i.e. restricted mobility group (caged animals) were remobilized for another 4 weeks. The generalized body weight and mid thigh circumference of all the animals were taken at the start of experiment, at the end of 4 weeks of immobilization and at the end of 4 weeks of remobilization in all groups. Results: Immobilization caused significant reduction in the body weight and mid thigh circumference of both the experimental groups. On remobilization the body weight increased but significant difference remained between the experimental and control groups. Although weight gain is more in the caged animals during remobilization phase but statistically insignificant difference was found when free & restricted mobility groups were compared. The difference in the mean mid thigh circumference between control and free mobility groups was statistically insignificant whereas the difference between control and restricted mobility groups was significant at the end of 4 weeks of remobilization. Recovery in caged animals was slower as compared to free mobility group in terms of mid thigh circumference but when these two groups were compared statistically insignificant difference existed at the end of 8 weeks. Conclusion: Immobilization induced reduction in body weight and mid thigh circumference which is to a great extent reversible in both free and restricted mobility groups. Both the groups responded almost equally to immobilization stress and confinement did not prevent restoration of bodyweight and mid thigh circumference, however complete recovery of the body weight and mid thigh circumference to initial control values did not occur in 4 weeks.